A recycling method for extracting lithium, copper and aluminum from waste lithium iron phosphate batteries
Through primary tooth cutting and crushing and inorganic trivalent iron salt solution leaching technology, the problems of excessive aluminum impurities and strong acid use in traditional lithium iron phosphate battery recycling are solved, and efficient and environmentally friendly lithium, copper and aluminum recycling is achieved, reducing production costs.
Patent Information
- Application Number
- CN202411734875.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the traditional lithium iron phosphate battery recycling method, crushing and sorting leads to excessive aluminum impurities, the use of strong acids in hydrometallurgy increases cost and environmental pressure, and the lithium recovery rate is low.
The waste lithium iron phosphate battery is treated with one-time tooth cutting and crushing to reduce the generation of fine aluminum powder, and leaching is used to use inorganic trivalent iron salt solution, and the peeling and sorting process is eliminated, so as to simplify the process flow.
It greatly reduces production costs and environmental impacts, improves the recovery and purity of lithium, copper and aluminum, and simplifies the process flow.
Smart Images

Figure CN119220819B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery recycling, and in particular to a recycling method for extracting lithium, copper and aluminum from waste lithium iron phosphate batteries. Background Art
[0002] As market demand increases, the number of new energy vehicles is also increasing. The sales of new energy vehicles have driven the installation of power batteries, showing a strong growth momentum.
[0003] At the same time, how to recycle lithium iron phosphate batteries after retirement has also become an important research topic. The main valuable metals in lithium iron phosphate are lithium, copper and aluminum. Effective and safe recycling of lithium iron phosphate can not only avoid environmental pollution, but also solve the problem of raw material sources for lithium power battery manufacturing.
[0004] The current method for recycling used lithium iron phosphate batteries in the industry is generally to first use a crushing and sorting method to obtain black powder, and then use a hydrometallurgical process to leach the black powder to recover lithium.
[0005] The traditional crushing and sorting method is to use a multi-stage crushing and screening process for waste lithium batteries, which leads to excessive crushing of the positive electrode current collector aluminum foil and the mixing of fine aluminum powder into black powder, resulting in excessive aluminum. Secondly, multiple crushing and screening may cause electrode materials to overflow into the environment, and the electrode material recovery rate is difficult to reach above 98.5%.
[0006] The hydrometallurgy of lithium iron phosphate black powder generally adopts the acid leaching process, such as China's inventions CN113603119 B and CN111285341 A. The acid leaching process requires a large amount of inorganic strong acid to dissolve the black powder. The inorganic acids used in industrialization are sulfuric acid, hydrochloric acid, phosphoric acid, etc., and sodium hydroxide is used to adjust the pH value later. These strong acids and strong alkalis are all hazardous chemicals. On the one hand, inorganic strong acids and strong alkalis are highly corrosive to equipment, and the equipment material requirements are high, which increases the costs of production processes, equipment, wastewater recycling and treatment. On the other hand, inorganic strong acids have no selectivity in dissolving metals. Due to the above-mentioned multiple crushing reasons, black powder containing too many metal impurities will dissolve impurities such as aluminum into the leachate during leaching. When removing aluminum during the hydrometallurgical process, the lithium element will be mixed into the slag phase by insoluble aluminum composite compounds, resulting in a decrease in the recovery rate of lithium. Therefore, for black powder containing excessive aluminum impurities, it is generally necessary to add an alkali dissolution aluminum removal process before leaching, such as Chinese invention CN 112441571 A. The alkali dissolution aluminum removal process can achieve a good aluminum removal effect, but the added alkali dissolution aluminum removal process will increase production costs.
[0007] In short, in the traditional recycling process of waste lithium iron phosphate batteries, the black powder electrode material contains excessive aluminum impurities, and the use of strong acid in hydrometallurgy increases the process cost and wastewater treatment cost, while also leading to an increase in the comprehensive energy consumption of lithium carbonate product production. Summary of the invention
[0008] In view of the technical problems existing in the above-mentioned prior art, the present invention provides a recovery method for extracting lithium, copper and aluminum from waste lithium iron phosphate batteries, which has the advantages of environmental protection, high efficiency and short process.
[0009] The technical solution adopted by the present invention is: to perform tooth cutting and crushing on the waste lithium iron phosphate battery once to avoid multiple crushing to produce too much fine aluminum powder; then to reduce the amount and perform environmentally friendly treatment to obtain a mixture of flaky positive and negative electrode sheets, and subsequently cancel the stripping and sorting steps in the traditional crushing and sorting method, and use an inorganic trivalent iron salt solution to directly start leaching from the mixture of positive and negative electrode sheets; the trivalent iron salt leaching process has good selectivity, the aluminum and copper of the positive electrode current collector are insoluble in the trivalent iron salt, the leachate has few impurities, the subsequent impurity removal cost is simplified, and a large amount of strong acid and strong alkali will not be consumed; after the leaching agent is simply regenerated, it can be recycled and reused for leaching; specifically, the following steps are included:
[0010] S1. First, the waste lithium iron phosphate battery is pretreated to obtain a mixture of positive and negative electrode sheets;
[0011] S2. Leaching the positive and negative electrode mixture using a solution of a trivalent iron salt as a leaching agent, and then filtering and separating to obtain a leachate containing lithium and divalent iron ions and a solid slag including positive and negative electrode current collectors and iron phosphate;
[0012] S3. The leachate containing lithium and divalent iron ions is oxidized by passing oxygen-enriched air, and a lithium hydroxide solution is added to adjust the pH value to between 4.0 and 4.5 to produce iron hydroxide precipitation, which is then filtered and separated to obtain a purified lithium-containing solution and an iron hydroxide solid phase;
[0013] S4. The purified lithium-containing solution is further treated with lithium hydroxide solution to adjust the pH value to 9 to 11, and then precipitated and crystallized by adding a saturated sodium carbonate solution under heating conditions to obtain industrial grade lithium carbonate;
[0014] S5. Add dilute acid to the solid phase of ferric hydroxide obtained in S3 to prepare a trivalent iron salt solution, and return to S2 for leaching process;
[0015] S6. The solid slag including the positive and negative current collectors and iron phosphate obtained in S2 is washed with a portion of the crystallization mother liquor of S4, then washed with hot water, and separated by a hydrodynamic screening device to obtain a mixture of copper and aluminum current collectors and a slag phase of iron phosphate;
[0016] S7. Dry and grind the mixture of copper and aluminum current collectors obtained in S6, and separate them using a specific gravity separator to obtain copper powder and aluminum powder.
[0017] Furthermore, in S1, the pretreatment is a reduction and environmentally friendly treatment, which means that under a nitrogen atmosphere, the waste lithium iron phosphate batteries are subjected to a toothed shear crushing and pyrolysis, and the electrolyte and diaphragm in the waste batteries are completely carbonized and volatilized, and then the shell and pile head are removed by air separation, and the exhaust gas is subjected to secondary combustion environmental protection treatment before meeting the emission standards.
[0018] Furthermore, the electrode pieces are in regular flakes after one-time shearing and crushing, and the content of fine metal powder, especially aluminum powder, in the material can be greatly reduced compared with multi-stage crushing or fine grinding; the size of the flaky positive and negative electrode pieces is controlled at 10~45mm; the pyrolysis temperature is 300~600℃, preferably 350~550℃.
[0019] Furthermore, in S2, the ferric salt is at least one of ferric sulfate, ferric chloride, and ferric nitrate; the molar number of ferric iron in the ferric salt solution is 25-50% of the molar number of lithium iron phosphate in the positive and negative electrode sheet mixture, and the liquid-to-solid mass ratio of the ferric salt solution to the positive and negative electrode sheet mixture is 3-10:1.
[0020] Furthermore, in S2, during the leaching reaction, the pH value of the reaction material is controlled in the range of 2.0 to 2.5 by gradually adding trivalent iron salt powder in small amounts.
[0021] Furthermore, in S2, the leaching reaction is specifically as follows: the leaching temperature is controlled at 20-40°C (normal temperature range), the trivalent iron salt solution and the positive and negative electrode plate mixture are stirred and reacted for 10-30 minutes, and then oxygen-enriched air is introduced for oxidation and stirring for 20-30 minutes, and then the oxygen-enriched air is stopped, and the stirring reaction is continued for 20-30 minutes before the reaction is terminated.
[0022] The reaction equation of the leaching process (taking iron sulfate as an example):
[0023] 2LiFePO4 + Fe2(SO4)3 = 2FeSO4 + Li2SO4 +2FePO4
[0024] The structure of lithium iron phosphate belongs to olivine type, in which the valence of iron is divalent, and the theoretical molar amount of trivalent iron salt is half of the molar amount of lithium iron phosphate. In S2, the molar amount of trivalent iron salt is 25-50% of the molar amount of lithium iron phosphate, and preferably the molar amount of trivalent iron salt is 25% of the molar amount of lithium iron phosphate. After the trivalent iron ions are consumed in the oxidized lithium iron phosphate, oxygen-rich air is introduced to oxidize the generated divalent iron ions into trivalent iron ions, and the trivalent iron ions can continue to leach the lithium iron phosphate.
[0025] Furthermore, in S3 and S4, the concentration of the lithium hydroxide solution is 1-10 mol / L, and the solution temperature is 20-60°C.
[0026] Furthermore, in S4, the heating temperature of adding the saturated sodium carbonate solution is 40-90°C.
[0027] Furthermore, in S4, the mother liquor after precipitation and crystallization of lithium carbonate is evaporated and concentrated, and then used to prepare lithium hydroxide solution.
[0028] Furthermore, in S5, the concentration of the dilute acid is 0.1-2 mol / L, and the dilute acid is one of sulfuric acid, hydrochloric acid or nitric acid. The prepared trivalent iron salt solution is returned to the leaching process and recycled for leaching of the mixture of waste lithium iron phosphate positive and negative electrode sheets.
[0029] Furthermore, oxygen-enriched air is a by-product of the nitrogen generator of the crushing and sorting line when producing nitrogen, and the volume fraction of oxygen in the oxygen-enriched gas is 26%~32%.
[0030] Furthermore, in S6, the hydrodynamic screening equipment is a hydrodynamic screening container with a built-in screen, the screen aperture is 3-8 mm, the screen hole spacing is 5-10 mm, and the mixture of copper, aluminum collectors and iron phosphate slag is mixed with water into a slurry, which is then pumped into the hydrodynamic screening equipment through the screen, and the copper, aluminum collectors are separated from the iron phosphate slag; the iron phosphate-containing slurry separated by the hydrodynamic screening equipment is filtered and dried to obtain iron phosphate slag, and the filtrate can be recycled and reused to prepare the slag phase separated in S2 into a slurry.
[0031] Furthermore, in S7, the gravity separator separates the copper powder and aluminum powder according to the difference in specific gravity of the copper and aluminum metal powders, and the purity of the copper and aluminum powders is ≥99%.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The crushing and sorting at the beginning of the waste lithium iron phosphate battery recycling process of the present invention only requires the mixture of positive and negative electrode sheets, eliminating the subsequent stripping and sorting steps commonly used in the crushing and sorting line. The positive and negative electrode sheets directly enter the wet process, which greatly reduces the investment in the production line and the production cost. On the other hand, the leaching process of the positive and negative electrode sheets is carried out in an aqueous medium, eliminating the possible excessive crushing of aluminum in the conventional practice of dry stripping of the electrode sheets, resulting in excessive aluminum impurities and dust overflow losses during sorting.
[0034] (2) The present invention uses a non-acidic trivalent iron salt solution for leaching, which is completely different from the strong acid leaching process commonly used in the industry. First, there is no strong acid or alkali, and the process and storage and transportation are safe and environmentally friendly. Second, the leaching process has better selectivity, and metal impurities such as aluminum and copper are basically not dissolved in the solution, reducing the subsequent impurity removal cost. Third, the leaching process is under normal temperature and pressure, does not require high temperature, and has low production cost. The purified lithium-containing solution has high purity, and the lithium carbonate obtained by sodium carbonate precipitation can reach industrial grade purity.
[0035] (3) The present invention uses oxygen-enriched air with lower cost to oxidize divalent iron ions. Oxygen-enriched air is a byproduct of the nitrogen generator and is normally discharged directly. The present invention uses the byproduct of the nitrogen generator in the crushing and sorting line equipment to oxidize divalent iron, thereby reducing the production and operation costs.
[0036] (4) In conventional hydrometallurgy, sodium hydroxide is often used as a strong base to adjust the pH value. Since a strong acid is used as the leaching agent, a large amount of sodium hydroxide is required, and other ions are introduced into the system, increasing the subsequent separation cost. The present invention uses lithium hydroxide solution to adjust the pH value of the leachate. Lithium ions do not need to be separated and are an important component of lithium carbonate, thereby reducing production and operation costs.
[0037] (5) The present invention aims to recover high-purity copper and aluminum powders, and does not recover iron phosphate slag. This is because the market prices of copper powder and aluminum powder are much higher than the latter, and the equipment investment and production costs of copper and aluminum recovery equipment are relatively low, while the equipment investment and production costs of iron phosphate recovery to meet the quality requirements of battery-grade iron phosphate are very high. At present, the market value of iron phosphate does not match the equipment investment and operating costs. The present invention treats it as general solid waste and can be considered as a raw material for infrastructure materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited thereto.
[0040] The process flow diagram of the present invention is as follows Figure 1 As shown, the following examples are used for specific illustration. Example 1
[0041] The waste lithium iron phosphate square aluminum shell battery is conveyed to the shear crusher through the material conveyor belt for crushing. The crushed material enters the pyrolysis furnace for pyrolysis for 1 hour. The pyrolysis temperature is controlled at 450℃. The above crushing and pyrolysis processes are provided with nitrogen atmosphere by the nitrogen generator. The out-of-furnace material first passes through a vibrating linear screen to screen and separate a small amount of black powder, and then separates the heavy shell and pile head through air separation to obtain a mixture of positive and negative electrodes. The mixture of positive and negative electrodes and a small amount of black powder screened out by the linear screen are mixed with water into a concentrated slurry and transported to the leaching tank. The ferric sulfate solution is added and stirred. The material temperature is controlled within the normal temperature range of about 25℃, reacted for 30 minutes, and then oxygen-enriched air is introduced for oxidation for 30 minutes, and then stirred for leaching reaction for 30 minutes. Then filter and wash to obtain the leachate and leaching residue. Weigh and detect the lithium content in the leachate and leaching residue. The analysis shows that the leaching rate of lithium is 97.6%, and the leaching rates of aluminum and copper are 0.4% and 0.5%, respectively.
[0042] The oxygen-enriched air produced by the nitrogen generator is passed into the leaching solution for 1 hour, the oxygen-enriched air is stopped, and then a 2 mol / L lithium hydroxide solution is slowly added to adjust the pH value of the solution to 4.5 to produce iron hydroxide precipitate, which is filtered and separated to obtain the purified lithium-containing leaching solution and iron hydroxide precipitate. The iron hydroxide precipitate is added with 1 mol / L dilute sulfuric acid to form an iron sulfate solution with a pH value in the range of 1.0 to 1.5, which is returned to the leaching process for the leaching of the positive and negative electrode mixture of lithium iron phosphate.
[0043] The purified lithium-containing solution is then added with lithium hydroxide solution until the pH value of the solution is 11. The solution is filtered to remove impurities, the filtrate is heated to about 85°C, and then a saturated sodium carbonate solution is added. The reaction is continued for 1 hour, and crystals are generated after cooling. After filtration and hot water washing, industrial-grade lithium carbonate is obtained, and its purity is analyzed to be 99.35%. After crystallization, the mother liquor is evaporated and concentrated, and the concentrated mother liquor is returned to the purified lithium-containing solution to adjust the pH value of the solution.
[0044] The leached residue after leaching of the positive and negative lithium iron phosphate plates is a mixture of copper, aluminum current collectors and solid iron phosphate slag. After being prepared into slurry, the copper and aluminum current collectors are separated by hydrodynamic screening equipment. After drying and grinding, copper powder and aluminum powder are separated by a specific gravity separator. The recovery rate of copper and aluminum powder is 98.5%, and the purity of copper and aluminum powder is above 99%. Example 2
[0045] The waste lithium iron phosphate cylindrical battery is conveyed to the shear crusher through the material conveyor belt for crushing. The crushed material enters the pyrolysis furnace for pyrolysis for 1 hour. The pyrolysis temperature is controlled at 400℃. The above crushing and pyrolysis processes are provided with nitrogen atmosphere by the nitrogen generator. The material out of the furnace first passes through a vibrating linear screen to screen and separate a small amount of black powder, and then through air separation, the heavy shell and pile head are separated to obtain a mixture of positive and negative electrodes. The mixture of positive and negative electrodes and a small amount of black powder screened out by the linear screen are mixed with water to form a concentrated slurry and transported to the leaching tank. The ferrous sulfate solution is added and stirred, and the material temperature is controlled at about 25℃. The reaction is carried out for 25 minutes, and then oxygen-enriched air is introduced for oxidation for 30 minutes, and then stirred for leaching reaction for 30 minutes. Then filter and wash to obtain the leachate and leaching residue. Weigh and detect the lithium content in the leachate and leaching residue. The analysis shows that the leaching rate of lithium is 97.8%, and the leaching rates of aluminum and copper are 0.4% and 0.5%, respectively.
[0046] The oxygen-enriched air produced by the nitrogen generator is passed into the leaching solution for 1 hour, and the oxygen-enriched air is stopped. A 2 mol / L lithium hydroxide solution is slowly added to adjust the pH value of the solution to 4.5 to produce iron hydroxide precipitate, which is filtered and separated to obtain the purified lithium-containing leaching solution and iron hydroxide precipitate. The iron hydroxide precipitate is added with 1 mol / L dilute sulfuric acid to form an iron sulfate solution with a pH value in the range of 1.0 to 1.5, and then returned to the leaching process for the leaching of the positive and negative electrode mixture of lithium iron phosphate.
[0047] The purified lithium-containing solution is then added with lithium hydroxide solution until the pH value of the solution is 11. The solution is filtered to remove impurities, the filtrate is heated to about 85°C, and then a saturated sodium carbonate solution is added. The reaction is continued for 1 hour, and crystals are generated after cooling. After filtration and hot water washing, industrial-grade lithium carbonate is obtained, and its purity is analyzed to be 99.4%. After crystallization, the mother liquor is evaporated and concentrated, and the concentrated mother liquor is returned to the purified lithium-containing solution to adjust the pH value of the solution.
[0048] The leached residue after leaching of lithium iron phosphate positive and negative electrodes is a mixture of copper, aluminum current collectors and solid iron phosphate slag. After being prepared into slurry, the copper and aluminum current collectors are separated by hydrodynamic screening equipment. After drying and grinding, copper powder and aluminum powder are separated by a specific gravity separator. The recovery rate of copper and aluminum powder is 98.5%, and the purity of copper and aluminum powder is above 99%.
Claims
1. A method for recovering lithium, copper and aluminum from waste lithium iron phosphate batteries, characterized in that: The steps include: S1. First, the waste lithium iron phosphate battery is pretreated to obtain a mixture of positive and negative electrode sheets; S2. Leaching the positive and negative electrode mixture using a solution of a trivalent iron salt as a leaching agent, and then filtering and separating to obtain a leachate containing lithium and divalent iron ions and a solid slag including positive and negative electrode current collectors and iron phosphate; S3. The leachate containing lithium and divalent iron ions is oxidized by passing oxygen-enriched air, and a lithium hydroxide solution is added to adjust the pH value to between 4.0 and 4.5 to produce iron hydroxide precipitation, which is then filtered and separated to obtain a purified lithium-containing solution and an iron hydroxide solid phase; S4. The purified lithium-containing solution is further treated with lithium hydroxide solution to adjust the pH value to 9 to 11, and then precipitated and crystallized by adding a saturated sodium carbonate solution under heating conditions to obtain industrial grade lithium carbonate; S5. Add dilute acid to the solid phase of ferric hydroxide obtained in S3 to prepare a trivalent iron salt solution, and return to S2 for leaching process; S6. The solid slag including the positive and negative current collectors and iron phosphate obtained in S2 is washed with a part of the crystallization mother liquor of S4, then washed with hot water, and separated by a hydrodynamic screening device to obtain a mixture of copper and aluminum current collectors and a slag phase of iron phosphate; S7. The mixture of copper and aluminum current collectors obtained in S6 is dried and ground, and then separated by a gravity separator to obtain copper powder and aluminum powder; In S1, the pretreatment is a reduction and environmental protection treatment, which means that in a nitrogen atmosphere, the waste lithium iron phosphate battery is subjected to a tooth shearing crushing and pyrolysis, and the electrolyte and diaphragm in the waste battery are completely carbonized and volatilized, and then the shell and pile head are removed by air separation, and the tail gas is subjected to secondary combustion environmental protection treatment and meets the emission standards; the size of the sheet-shaped positive and negative electrode sheets obtained after the tooth shearing crushing is controlled at 10~45mm; the pyrolysis temperature is 300~600℃; In S2, the leaching reaction is specifically as follows: the leaching temperature is controlled at 20-40°C, the trivalent iron salt solution and the mixture of the positive and negative electrode sheets are stirred and reacted for 10-30 minutes, and then oxygen-enriched air is introduced for oxidation and stirring for 20-30 minutes, and then the oxygen-enriched air is stopped, and the stirring reaction is continued for 20-30 minutes before the reaction is terminated; during the leaching reaction, the pH value of the reaction material is controlled to be in the range of 2.0-2.5 by adding trivalent iron salt powder in small amounts and gradually; The oxygen-enriched air is a byproduct of the nitrogen generator of the crushing and sorting line when producing nitrogen, and the volume fraction of oxygen in the oxygen-enriched gas is 26% to 32%.
2. The method for recovering lithium, copper and aluminum from waste lithium iron phosphate batteries according to claim 1, characterized in that: In S2, the ferric salt is at least one of ferric sulfate, ferric chloride, and ferric nitrate; the molar number of ferric iron in the ferric salt solution is 25-50% of the molar number of lithium iron phosphate in the positive and negative electrode sheet mixture, and the liquid-to-solid mass ratio of the ferric salt solution to the positive and negative electrode sheet mixture is 3-10:
1.
3. The method for recovering lithium, copper and aluminum from waste lithium iron phosphate batteries according to claim 1, characterized in that: In S3 and S4, the concentration of the lithium hydroxide solution is 1-10 mol / L, and the solution temperature is 20-60°C.
4. The method for recovering lithium, copper and aluminum from waste lithium iron phosphate batteries according to claim 1, characterized in that: In S4, the heating temperature of adding saturated sodium carbonate solution is 40-90°C, and the mother liquor after precipitation of crystallized lithium carbonate is used to prepare lithium hydroxide solution after evaporation and concentration.
5. The method for recovering lithium, copper and aluminum from waste lithium iron phosphate batteries according to claim 1, characterized in that: In S5, the concentration of the dilute acid is 0.1~2 mol / L, and the dilute acid is one of sulfuric acid, hydrochloric acid or nitric acid.
6. The method for recovering lithium, copper and aluminum from waste lithium iron phosphate batteries according to claim 1, characterized in that: In S6, the hydrodynamic screening device is a hydrodynamic screening container with a built-in screen, the screen aperture is 3-8 mm, and the screen aperture spacing is 5-10 mm.
Citation Information
Patent Citations
Method for extracting battery-grade iron phosphate from waste lithium iron phosphate battery
CN111285341A
Recovery method of high-aluminum lithium iron phosphate waste
CN112441571A
A method for recovering lithium from waste lithium iron phosphate materials
CN113603119B
Method for comprehensive recycling waste lithium iron phosphate battery cathode material
CN110474123A
Waste gas reduction and harmlessness treatment method in waste lithium battery recycling process
CN114100318A
Cited By
Integrated wet method for low-waste high-valued recovery of lithium iron phosphate battery mixed powder
CN121948508A